Fertility Research and Practice - Schust, Danny; Ginsburg, Elizabeth S.
Fertility Research and Practice is a peer-reviewed, open access, online journal, publishing articles that provide novel insights into male and female infertility and early pregnancy. Articles include basic, clinical, and translational work, including case reports and reviews. Fertility Research and Practice aims to elucidate the broad range of topics comprising the study of human fertility and early pregnancy. These include diagnosis and correction of endometriosis, congenital and acquired abnormalities of the male and female reproductive tracts, reproductive infectious diseases, male and female fertility diagnostics, assisted reproductive techniques (ART), implantation and early pregnancy failure, pregnancy of unknown location, and sporadic and recurrent pregnancy loss. Understanding that the study of human fertility and early pregnancy often involves in vitro, ex vivo and animal models for ethical and legal reasons, Fertility Research and Practice invites basic science in addition to clinical and translational research. Approaches that apply cutting-edge technologies to problems in the field are especially welcome.